2009
DOI: 10.3892/or_00000489
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-1α expression predicts the response to 5-fluorouracil-based adjuvant chemotherapy in advanced gastric cancer

Abstract: Abstract. Hypoxia frequently occurs in various solid tumors, thereby accelerating cancer progression and treatment resistance. Hypoxia-inducible factor-1· (HIF-1·) plays a central role in tumor hypoxia by up-regulating the gene expression related to angiogenesis, cancer invasion and anti-apoptosis. The present study immunohistochemically investigated HIF-1· expression in 63 gastric cancer specimens. Those specimens were obtained from 44 patients that received 5-FU chemotherapy post-operatively whereas the rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Even if HIF-1α-dependent molecular mechanisms in chemo-sensitivity have been only partially elucidated, suppression of p53 and activation of nuclear factor κB (NF-κB) seem to play a key role in hypoxia-related 5-fluorouracil (5-FU) and cisplatin (CDDP) sensitivity in human GC cells [49]. It has been reported that HIF-1α induces drug resistance to adjuvant chemotherapy with 5-FU in advanced GC patients [50]. Moreover, the overexpression of HIF-1α leads to hypoxia-induced drug resistance by increasing the expression of Bcl-2, P-glycoprotein (P-gp) and MRP1, and reducing the expression of Bax [51].…”
Section: Role Of Microenvironment In Tumor Growth and Chemo-resistmentioning
confidence: 99%
“…Even if HIF-1α-dependent molecular mechanisms in chemo-sensitivity have been only partially elucidated, suppression of p53 and activation of nuclear factor κB (NF-κB) seem to play a key role in hypoxia-related 5-fluorouracil (5-FU) and cisplatin (CDDP) sensitivity in human GC cells [49]. It has been reported that HIF-1α induces drug resistance to adjuvant chemotherapy with 5-FU in advanced GC patients [50]. Moreover, the overexpression of HIF-1α leads to hypoxia-induced drug resistance by increasing the expression of Bcl-2, P-glycoprotein (P-gp) and MRP1, and reducing the expression of Bax [51].…”
Section: Role Of Microenvironment In Tumor Growth and Chemo-resistmentioning
confidence: 99%
“…Chemotherapy combined with sorafenib can effectively reduce serum HIF-1α and VEGF levels in patients with GC to improve their 1-year survival rate and prognosis ( 116 ). Diffuse expression of HIF-1α in gastric tumors may lead to resistance to adjuvant chemotherapy with 5-FU ( 163 ). Local amplification of associated genes ARID1A, PIK3CA, and P53, as well as HMGA2 and MET, also benefited from sorafenib treatment ( 112 ).…”
Section: Response Biomarkers Of Anti-angiogenic Drug Therapymentioning
confidence: 99%